1999
DOI: 10.1017/s1355838299982213
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of functional features of U6atac and U12 snRNAs between vertebrates and higher plants

Abstract: Splicing of U12-dependent introns requires the function of U11, U12, U6atac, U4atac, and U5 snRNAs. Recent studies have suggested that U6atac and U12 snRNAs interact extensively with each other, as well as with the pre-mRNA by Watson-Crick base pairing. The overall structure and many of the sequences are very similar to the highly conserved analogous regions of U6 and U2 snRNAs. We have identified the homologs of U6atac and U12 snRNAs in the plant Arabidopsis thaliana. These snRNAs are significantly diverged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 31 publications
4
80
0
Order By: Relevance
“…We have previously developed an in vivo mutational suppressor assay for the function of several of the snRNAs involved in U12-dependent splicing (Hall & Padgett, 1996;Kolossova & Padgett, 1997;Incorvaia & Padgett, 1998;Shukla & Padgett, 1999)+ This assay relies on the genetic suppression of splicing defects due to splice site mutations in a U12-dependent intron by coexpression of compensatory mutant snRNAs+ For U6atac snRNA, a mutation in the 59 splice site of a transfected minigene construct, which blocks splicing at the normal sites, is suppressed by cotransfection of expression constructs containing compensatory mutations in U11 and U6atac snRNAs+ The elements of this assay are diagramed in Figure 1B+ The P120 minigene contains a double mutation in positions 5 and 6 of the 59 splice site of the U12-dependent intron F (P120 CC5/ 6GG)+ This mutation causes a complete loss of splicing activity at the normal 59 and 39 splice sites and the concomitant activation of a pair of cryptic splice sites within the intron (Kolossova & Padgett, 1997)+ In vitro FIGURE 2. Comparison of the intramolecular stem-loop structures of various U6 and U6atac snRNAs+ The sequences are from human, A. thaliana (plant), and Saccharomyces cerevisiae (yeast)+ In each case the putative helix Ib interactions with the conspecific U2 or U12 snRNAs are shown below the intramolecular structures+ The boxed sequences are those that were substituted into the human U6atac snRNA in our previous analysis of the plant U6atac stem-loop (Shukla & Padgett, 1999) or in the work discussed here+ analysis has shown that this cryptic splicing reaction is catalyzed by the U2-dependent spliceosome (Tarn & Steitz, 1996a)+ Cotransfection of U6atac and U11 snRNA expression constructs that contain the compensatory mutations shown in Figure 1B restores U12-dependent splicing at the normal 59 and 39 splice sites to nearly wild-type levels+ This suppression is completely dependent on the U6atac suppressor while the U11 suppressor improves the level of suppression (Incorvaia & Padgett, 1998)+ This dependence on the addition of an exogenous suppressor U6atac allows us to assay the in vivo effects of mutations at other sites in U6atac snRNA+…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously developed an in vivo mutational suppressor assay for the function of several of the snRNAs involved in U12-dependent splicing (Hall & Padgett, 1996;Kolossova & Padgett, 1997;Incorvaia & Padgett, 1998;Shukla & Padgett, 1999)+ This assay relies on the genetic suppression of splicing defects due to splice site mutations in a U12-dependent intron by coexpression of compensatory mutant snRNAs+ For U6atac snRNA, a mutation in the 59 splice site of a transfected minigene construct, which blocks splicing at the normal sites, is suppressed by cotransfection of expression constructs containing compensatory mutations in U11 and U6atac snRNAs+ The elements of this assay are diagramed in Figure 1B+ The P120 minigene contains a double mutation in positions 5 and 6 of the 59 splice site of the U12-dependent intron F (P120 CC5/ 6GG)+ This mutation causes a complete loss of splicing activity at the normal 59 and 39 splice sites and the concomitant activation of a pair of cryptic splice sites within the intron (Kolossova & Padgett, 1997)+ In vitro FIGURE 2. Comparison of the intramolecular stem-loop structures of various U6 and U6atac snRNAs+ The sequences are from human, A. thaliana (plant), and Saccharomyces cerevisiae (yeast)+ In each case the putative helix Ib interactions with the conspecific U2 or U12 snRNAs are shown below the intramolecular structures+ The boxed sequences are those that were substituted into the human U6atac snRNA in our previous analysis of the plant U6atac stem-loop (Shukla & Padgett, 1999) or in the work discussed here+ analysis has shown that this cryptic splicing reaction is catalyzed by the U2-dependent spliceosome (Tarn & Steitz, 1996a)+ Cotransfection of U6atac and U11 snRNA expression constructs that contain the compensatory mutations shown in Figure 1B restores U12-dependent splicing at the normal 59 and 39 splice sites to nearly wild-type levels+ This suppression is completely dependent on the U6atac suppressor while the U11 suppressor improves the level of suppression (Incorvaia & Padgett, 1998)+ This dependence on the addition of an exogenous suppressor U6atac allows us to assay the in vivo effects of mutations at other sites in U6atac snRNA+…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the intramolecular stem-loop structures of various U6 and U6atac snRNAs+ The sequences are from human, A. thaliana (plant), and Saccharomyces cerevisiae (yeast)+ In each case the putative helix Ib interactions with the conspecific U2 or U12 snRNAs are shown below the intramolecular structures+ The boxed sequences are those that were substituted into the human U6atac snRNA in our previous analysis of the plant U6atac stem-loop (Shukla & Padgett, 1999) or in the work discussed here+ analysis has shown that this cryptic splicing reaction is catalyzed by the U2-dependent spliceosome (Tarn & Steitz, 1996a)+ Cotransfection of U6atac and U11 snRNA expression constructs that contain the compensatory mutations shown in Figure 1B restores U12-dependent splicing at the normal 59 and 39 splice sites to nearly wild-type levels+ This suppression is completely dependent on the U6atac suppressor while the U11 suppressor improves the level of suppression (Incorvaia & Padgett, 1998)+ This dependence on the addition of an exogenous suppressor U6atac allows us to assay the in vivo effects of mutations at other sites in U6atac snRNA+…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations